Do the Trajectories of Bipolar Disorder and Schizophrenia Follow a Universal Staging Model? - Duffy, Anne (Can J Psychiatry, 2016)
OBJECTIVE: The purpose of this study is to address the question of whether a universal staging model of severe psychiatric disorders is a viable direction for future research by examining the extant literature. METHOD: A narrative review was conducted of the relevant historical, conceptual, and empirical literature pertaining to the clinical trajectory of bipolar disorder and schizophrenia and issues relevant to staging. RESULTS: There is substantive evidence that classic recurrent bipolar disorder is separable from schizophrenia on the basis of family history, developmental and clinical course, treatment response, and neurobiological findings. However, because of the intrinsic heterogeneity of diagnostic categories that has been amplified by recent changes in psychiatric taxonomy, key distinctions between the groups have become obfuscated. While mapping risk and illness markers to emerging psychopathology is a logical approach and may be of value for some psychiatric disorders and/or their clinical subtypes, robust evidence supporting identifiable stages per se is still lacking. Presently, even rudimentary stages such as prodromes cannot be meaningfully applied across different disorders and no commonalities can be found for the basis of universal staging. CONCLUSIONS: Advances in the prediction of risk, accurate early illness detection, and tailored intervention will require mapping biomarkers and other risk indicators to reliable clinical phases of illness progression. Given the capricious nature of mood and psychotic disorders, this task is likely to yield success only if conducted in narrowly defined subgroups of individuals at high risk for specific illnesses. This approach is diametrically opposite to that being promulgated by proponents of a universal staging model.